PERAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI DAN KEPUASAN KERJA GURU DI SD NEGERI PAGUMENGANMAS - Herlinda; Naris Setyowati; Noor Miyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the research is to analyze the principal’s role in increasing teacher’s motivasion and job satisfaction at Pagumenganmas State Elementary School. The background this research is low job satisfaction which is characterized by a lack of appreciation for teachers, low teacher achievement motivation and a lack of communication between principal and teacher which often causes misunderstandings in interpreting task orders. This indication reflects the teacher's lack of concern for what is mentioned, often complaining and always considering every job given to be complicated, no desire to be motivated and achieve, lack of responsibility, lack of work enthusiasm and motivation. This research uses a qualitative approach with descriptive methods, involving interviews, observation, and documentation as data collection techniques. The research results show that the principal acts as an effective leader in creating a conducive learning environment, managing administration, and building good relationships with teachers. Principals who can carry out their functions as educators, managers, administrators, supervisors and motivators can significantly increase teacher job satisfaction. In addition, the principal's support in rewards and professional development contributes to increased teacher motivation and performance. This research confirms that good principal leadership is very important in building a productive and harmonious school climate, which in turn has a positive impact on the quality of education at Pagumenganmas State Elementary School.